Legionella longbeachae pneumonia: Case report and review of reported cases in non-endemic countries. (2021) - Bell, Harrison; Chintalapati, Sai; Patel, Preet; Halim, Ameer; Kithas, Andrew; Schmalzle, Sarah A.
Highlights: Legionella pneumophila can cause severe atypical community acquired pneumonia. L. pneumophila is associated with exposure to industrial water systems, like air conditioning. L. longbeachae causes same illness but is uncommon in the United States. L. longbeachae is associated with exposure to compose or potting soil. L longbeachae is difficult to diagnose given rarity, lack of rapid test, and need for specialized culture. Abstract: Legionella longbeachae pneumonia is much less common than Legionella pneumophila pneumonia in most of the world and may evade timely diagnosis in settings that rely primarily on urine antigen testing, which detects Legionella pnuemophila serogroup 1 only. It is, however, widely recognized in Australia and New Zealand, where it is endemic and associated with exposure to compost and potting soils, rather than contaminated water systems as seen with L. pneumophila. L. longbeachae can cause a similar spectrum and severity of illness as L. pneumophila. Here we present a case of a 47-year-old man with L. longbeacheae necrotizing pneumonia following exposure to possibly contaminated soil from a wastewater treatment facility. Initial presentation included cough, chest pain, and dyspnea, and progressed to hypoxic respiratory failure, tension pneumothorax, and cardiac arrest. L. pneumophila urine antigen was negative, but bronchioalveolar lavage samples grew L. longbeachae on buffered charcoal yeast extract agar. A review of cases reported in the literature in non-endemic regions over a 20-year period identified 38 cases in Europe, 33 in Asia, and 8 in North America. Average age was 65, 65 % were male, and 35 % had potentially relevant environmental exposures. L. longbeachae should be considered in cases of severe community acquired pneumonia, particularly following a consistent environmental exposure or if initial testing for other pathogens is unrevealing. A thorough exposure history including questions about contact with potting soil or compost, and utilization of specialized agar for culture can both be key in identifying this pathogen.